The Interface between the State and Civil Society in Nepal - Bhatta, Chandra D. (Dhaulagiri Journal of Sociology and Anthropology, 2016)
The paper explores the state-civil society relations in Nepal, which have gone through many ups and downs from various perspectives. This is important for the reason that the two terms are now in the forefront of public debate: Rajya – the state and Nagarik Samaj – civil society. Voices, both in favour and against the state and civil society, are now audible everywhere. The debate has picked up momentum, particularly after the regime change of 2006, when civil society took a new birth and played a crucial role in regime. However, all is not well with the role of both state and civil society. The point at stake, however, is how should one describe the state-civil society relations in Nepal; how they influence, behave, and view each other; and where do they converge and diverge? These are some of the important issues that need to be looked into carefully. The rise of right-based civil society organisations (CSOs) in Nepal has further created confusion vis-a-vis state. Within these contexts, paper here attempts to explain the extant interface.